Precompetitive anxiety profiles in runners: Differences in the running motives - Prieto Andreu, Joel Manuel; González-García, Higinio (Journal of American College Health, 2023)
The study aimed to identify precompetitive anxiety profiles and analyze the impact of those profiles in their reasons to adhere to running. A sample of 473 Spanish Amateur Athletes participated in the study. Results revealed the emergence of three profiles: (a) a high precompetitive anxiety profile characterized by high cognitive and somatic anxiety and low self-confidence; (b) a precompetitive medium-low anxiety profile characterized by medium-low scores in cognitive and somatic anxiety and medium self-confidence; (c) a precompetitive low anxiety profile characterized by low scores in cognitive and somatic anxiety and medium self-confidence. Results showed that most of the working runners, who participate in ten-kilometer races, who practice three days a week, and most experienced runners, belonged to the extremely low anxiety profile. In conclusion, the precompetitive low anxiety profile reported the most suited outcomes which mean that is a more adaptive profile.
Keywords: cluster analysis; endurance; running; sport competition; Scopus; JCR